Angelo Maria Bandini in viaggio a Roma (1780-1781) - SABBA, FIAMMETTA (Biblioteche & bibliotecari / Libraries & librarians, 2019)
A rich cultural insight of Rome in the second half of the 18th century emerges from the edition of an autograph memoir on the journey from Florence to Southern Italy made by the librarian Angelo Maria Bandini (1780-1781). Lounges, coffees and chocolates, religious rites, curial relations and the reforming action by Pope Pious VI are the backdrop to the meticulous description of Rome as a 'diffused museum'. Bandini, librarian and scholar of the enlightenment century, visits and observes palaces, art galleries, cabinets and churches, paying particular attention to libraries, whose metaphorical sieve gives birth to remarkable pieces and precious curiosities.